Strategi Kekuasaan Bourdieu Tiktok Shop dalam Merebut Pasar Perdagangan di Indonesia - Farhana, Andi Tenri Ribi (Crises on Languages and Literature, 2024)
The characteristic of TikTok Shop, which is one of the modern online markets, lies in the variety of types of goods sold in it. This market, in addition to providing local goods, also presents imported goods. In addition, in terms of price, TikTok Shop has a definite price tag, including the price before and after tax. This price clarity provides certainty to consumers in making purchasing decisions. It is important to note that TikTok Shop not only acts as a place for buying and selling transactions, but also as a centre for shopping experiences with an emphasis on quality customer service. In relation to market dominance, this study investigates how TikTok Shop strategizes within Pierre Bourdieu's social power framework. Pierre Bourdieu developed several analytical strategies and concepts within his theoretical framework to understand the dynamics of social life. Some of the main strategies in his study involve concepts such as habitus, capital, realm, and arena. Here are some key strategies in Pierre Bourdieu's study. With modern management, this market becomes more efficient in its operations and is able to provide a comfortable and satisfying shopping experience for consumers who prioritize quality and comfort in shopping.